THE MODERN POETICAL SUBJECT BETWEEN NATURE AND CIVILIZATION – ANALYSIS OF THE POETRY COLLECTION OCTAVES BY MIODRAG PAVLOVIĆ (Philological Studies, 2025)
This paper analyzes Miodrag Pavlović’s poetry collection, Octaves. The research is focused on Pavlović’s understanding of the pastoral, as a classical poetic genre, which, in his treatment, expands its traditional chronotope to the urban area. Then, the research focus is directed at the relationship between nature and the city / civilization / culture, which is shaped in the consciousness and poetic expression of the lyrical subject whose thought is precisely defined in the dialectical conflict of the aforementioned opposing categories. The largest part of the analysis is directed towards understanding the archetypal imagery, which is confirmed in the numerous isomorphic permeations between the lyrical subject and nature. The undertaken immersion into the semantics and imagery of myth is not only an expression of the duality of the modern subject of Octaves, which is defined between nature and civilization, but also a significant poetic feature of Pavlović’s early poetry. The modernity of his poetry is revealed through the desire to present the identity of a modern subject who is torn between two forms that determine his consciousness and subconsciousness – nature and civilization. Also, this is seen through the poetic intention that the aforementioned conflict in the consciousness of the lyrical subject finds its expression through mythical thinking and archetypal representation, thereby confirming one of the fundamental poetic characteristics of Serbian poetry of post-war modernism – the reevaluation and reinterpretation of traditional codes, in this case, myth.
Keywords: poetics, poetry, myth, archetype, identity, modernity, nature, city, Octaves, Miodrag Pavlović